MEMBUMIKAN DYNAMIC GOVERNANCE DALAM MENINGKATKAN PROFESIONALISME MANAJEMEN PENYELENGGARAAN HAJI - Kusuma, Bayu Mitra Adhyatma (JPSI (Journal of Public Sector Innovations), 2016)
The purpose of this research is to contribute initiative ideas to improve the hajj management professionalism through dynamic governance. This research uses qualitative type with descriptive approach. The research results with concern to the culture and capability of the Ministry of Religious Affairs formulate that thinking ahead can be executed by analyzing and projecting what will be facing in 10 or 20 years into the future based on the tendency toward national and global change, political constellation, and socio-economic of the community. Thinking again can be done by reviewing again whether policies, strategies and programs that are running are appropriate and able to meet the needs of pilgrims. And Thinking across, can be applied by learning from the experiences of other countries that also regulates the organization of the Hajj.